Conversational Informatics A Data-Intensive Approach with Emphasis on Nonverbal Communication - Nishida, Toyoaki; Nakazawa, Atsushi; Ohmoto, Yoshimasa; Mohammad, Yasser (Springer Japan : Imprint: Springer, 2014)
This book covers an approach to conversational informatics which encompasses science and technology for understanding and augmenting conversation in the network age. A major challenge in engineering is to develop a technology for conveying not just messages but also underlying wisdom. Relevant theories and practices in cognitive linguistics and communication science, as well as techniques developed in computational linguistics and artificial intelligence, are discussed.